Behavioural abnormalities in children with nephrotic syndrome - Mishra, Om Prakash; Basu, Biswanath; Upadhyay, Shashi K.; Prasad, Rajniti; Schaefer, Franz (Nephrology, dialysis, transplantation, 2010)
Background. Glucocorticoid therapy in children with nephrotic syndrome can lead to many adverse effects including behavioural problems. The present study was undertaken to assess the changes in individual behaviour among different sub-groups of patients with idiopathic nephrotic syndrome (INS) and also to find out the relationship, if any, between different behavioural problems with cumulative dose of steroid therapy.Methods. This was a prospective hospital-based study. We assessed behavioural patterns in 131 children and adolescents with steroid-responsive INS aged 1.5-15 years. Fifty healthy children matched for age and gender were included to serve as controls. The Achenbach Child Behaviour Checklist was used to assess individual behaviour. Patients were sub-grouped according to age (1.5-5 and 6-15 years) and disease status (first attack before and after 12-week prednisolone, infrequent relapser, frequent relapser/steroid-dependent).Results. All groups had significantly elevated mean behavioural abnormality scores for dimensions assessed in both age groups, except rule-breaking behaviour. Besides sleep problems, frequent relapsers/steroid-dependent patients exhibited maximum scores in comparison to first attack and infrequent relapsers in the 1.5- to 5-year age group. Total and individual behavioural scores showed close associations with cumulative prednisolone dose in both groups.Conclusions. It is evident that nephrotic syndrome patients should be given due consideration in clinical practice for behavioural abnormalities especially after steroid therapy.